Non-Ferrous Melt Chemistry : The Role of Slags and Mattes - Grimsey, Eric (University of Melbourne, 1982)
This paper reviews the chemical and physical properties of iron silicate slags and mattes, especially those encountered in nickel and copper smelting, as well as the interactions between slag and matte which affect the outcome of smelting and converting processes. The topics covered include phase relationships and activities, viscosity and surface tension, as well as the factors affecting metal loss as a result of chemical dissolution and mechanical entrainment.